Performance of poly cultured fish species fed organic or commercial diets - Muelbert, Betina; Weingartner, Marcos; Sado, Ricardo Yuji; Ferrari, Fernanda; Borba, Maude Regina de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Polyculture with supplementary diets is considered a viable model for organic fish production, although is still a system on its infancy. The aim of the present study was to compare the performance of fishes in polyculture fed organic or commercial diets in an on-farm experiment in southern Brazil. In four farms, two dietary treatments were evaluated: pelleted Organic artisanal diet and extruded conventional Commercial diet. Polyculture was a combination of Rhamdia quelen (30%), Cyprinus carpio (20%), Pterygoplichthys joselimaianus (15%), Prochilodus lineatus (15%) Hypophthalmichthys molitrix (7,5%), H. nobilis (7,5%) and Ctenopharyngodon idella (5%). Juveniles were stocked in earthen ponds at a total density of 1.5 fish m-2 and fed for 12 months. Final biomass was significantly higher in the Organic (4,877.8 kg haha-1) than in the Commercial treatment (3,067.1 kg haha-1). Mean final weight, specific growth rate, fillet composition and total survival of fishes did not differ among treatments. In conclusion, feeding organic diets recorded bigger production and water quality than commercial diets in poly culture system. We hope that these results will stimulate further research on organic fish farming.